Comprehensive Analysis of Territorial Uses for the Development of Mining Degraded Areas: The Surrounding of Portmán (La Unión). - Esteve-Guirao, Patricia; Banos-González, Isabel; Baños-Páez, Pedro; Pérez-Cutillas, Pedro; Díez de Revenga-Martínez, Emilio; Martínez-Pedrero, Magdalena; Lluna-Diaz, María (Revista de Estudios Andaluces, 2017)
The Portmán Bay, Southeast Iberian Peninsula, is home to one of the largest environmental disasters on the Mediterranean coast: the silting of the bay caused by the dumping of million tonnes of mining waste to the sea, over more than thirty years. The analysis of the values of the surroundings, and the assessment of the potential for the development of the bay arises with the aim of obtaining alternatives for planning a sustainable local development and respectful with the environment. Two phases of analysis have been carried out: the first through a partial, more detailed, study; followed by a second phase of analysis, with an overall assessment of land uses to determine the constraints and development opportunities of the surroundings of Portmán. The integral analysis provides a vision of the space as a whole, and allows defining territorial categories in relation to possible developments in the form of residential and tourism projects, which are defined as: limitations, main constraints and additional constraints.